Examining Market Behavior of Minority Businesses: An Empirical Study on Market and Risk Behavior of Minority-Owned Business Enterprises - D. Anthony Miles; Josh Garcia; Eniola Olagundoye; Wanda Goodnough; dt ogilvie; E.L. Seay; Nathan Tymann; Robin Shedrick (New Advances in Business, Management and Economics Vol. 1, 2025)
The number of minority business owners and entrepreneurs is rising rapidly, and many are creating substantial business ventures. The research on the success, failure and survival of minority firms has been extensive and well-documented. The purpose of this study is to examine and measure market behavior and risk patterns of minority-owned business enterprises (MBE). A representative sample (N = 192) of MBEs was examined for this study. Building on key theoretical concepts grounded in accounting, economics, entrepreneurship, finance, marketing, and management literature (such as endogenous and exogenous forces), a researcher-developed instrument was used for this study. The researcher-developed Entrepreneurial Risk Assessment Scale (ERAS) was used for this study. The hypotheses derived from the theoretical framework were tested using empirical analysis of a representative sample of MBEs across various industries. The study utilizes a quantitative approach. The prior research on the performance of MBEs is limited. The research questions guiding this study were the following: (a) What are the market forces that affect minority business enterprises (MBE); and (b) how many factors affect the MBEs? The quantitative methodology used a multivariate statistical approach: a factor analysis was used for examining both endogenous and exogenous variables. Also, a factorial MANOVA was used. As a result of the principal component analysis (PCA), a seven-factor solution emerged from the statistical analyses. The findings of the study indicate that minority business enterprises (MBE) have similar, yet unique firm behavioral characteristics to their nonminority counterparts. The findings also suggest that there are no distinct differences between male MBEs and female MBES in terms of market patterns and risk patterns. The results of the study indicate there are seven factors that affect the market behavior of minority-owned businesses. Future research should focus on the market behavior of minority business enterprises on a local, state, and national level.